Obama and the emergence of a multipolar world order redefining U.S. foreign policy - Dolan, Chris J. (Lexington Books, 2018)
U.S. foreign policy under Obama would be defined by international and domestic pressures that shook the rules-based international order. In response to an increasingly multipolar system, Obama transitioned foreign policy away from U.S. hegemony toward a more scaled-back role that would culminate in the rise of Trump and America First.